Failure characteristics of unsaturated intact loess under different hydraulic pathways - Weiye Fu; Shengjun Shao; Aizhong Luo; Tao Li; Zijun Zhao (PLoS ONE, 2025)
This study systematically investigates the effects of two hydraulic pathways—wetting followed by loading (W-L) and loading followed by wetting (L-W)—on the water retention and strength characteristics of intact loess from a Xi’an metro line. Using an improved unsaturated triaxial testing system, experiments were conducted under controlled suction, net confining pressure, and shear stress levels. The Van Genuchten model accurately describes the water retention behavior, with the saturation-suction ratio (s/ S c ) exhibiting a linear relationship. The Critical State Line (CSL) for the L-W pathway exhibits a lower slope than that for the W-L pathway, indicating a reduction in shear strength and that hydraulic pathways strongly influence the suction contribution to loess strength. A threshold line in the q-p ’ plane is identified, suggesting that hydraulic effects must be considered when the pre-wetting stress state exceeds this threshold. Scanning electron microscopy (SEM) analysis combined with quantitative pore analysis reveals that W-L induces pore expansion and cement dissolution, while L-W promotes particle compaction, partial cement fragmentation, and a measurable refinement of the pore network.